Urgensi Perlindungan Lahan Pertanian Pangan Terhadap Alih Fungsi Lahan di Daerah Istimewa Yogyakarta - Gunawan Wibisono; Yeni Widowaty (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
One of the threats to achieving food security and sovereignty is the conversion of agricultural land functions because its application has an impact on food production, the physical environment, and the level of welfare of rural farmers whose livelihoods depend on their land which causes a decline in farmers' welfare. The conversion of agricultural land functions is also the cause of the limited area of cultivated land. Land conversion activities in the Special Region of Yogyakarta are increasing every year due to economic factors and population growth rates. The purpose of this study is to examine the urgency of protecting food agricultural land against land conversion in the Special Region of Yogyakarta and to propose future concepts related to the problems of existing land function specialists, especially in the Special Region of Yogyakarta. The research method is normative research and empirical research with primary, secondary and tertiary legal materials. The technique of taking legal materials in this study uses library research. Results and Conclusions: The form of expert protection for food agriculture land functions in the Special Region of Yogyakarta is regulated in